2014
DOI: 10.1007/s00246-014-0959-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Systolic Left Ventricular Function in Preterm and Term Neonates: Reference Values of the Mitral Annular Plane Systolic Excursion (MAPSE) and Calculation of z-Scores

Abstract: The mitral annular plane systolic excursion (MAPSE) is a quick and reliable echocardiographic tool for assessing longitudinal left ventricular (LV) systolic function in children and adults. Because this parameter is affected by the LV longitudinal dimension, pediatric and adult normal values are not suitable for preterm and term neonates. A prospective study investigated a large group of preterm and term neonates [gestational age (GA), 26/0-6 to 40/0-6; birth weight (BW), 670-4,140 g]. The growth- and BW-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…Koestenberger et al. showed that MAPSE in neonates correlated with both gestational age and birthweight . Erikson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koestenberger et al. showed that MAPSE in neonates correlated with both gestational age and birthweight . Erikson et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, less data are available for normal MAPSE values of children, including neonates. [9][10][11][12][13] Children have a smaller left ventricle and shorter MAPSE than adults. Differences in normal values for MAPSE with aging make it difficult to use MAPSE in actual clinical practice in pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies support the use of TAPSE and MAPSE as a sensitive tool for detecting subtle cardiac dysfunction in fe-tuses with IUGR [9] and twin-to-twin transfusion syndrome (TTTS) [10] . Reference values have been reported for adults [11,12] , children [13][14][15] and neonates [16,17] ; however, only a few studies [1,6,8] considering reference intervals for fetal TAPSE and MAPSE have been published. Most of them were based on gestational ages (GAs) and only one study provided centiles normalized to estimated fetal weight (EFW) [6] in order to overcome the disadvantage of using unreliable GA as an independent variable.…”
Section: Introductionmentioning
confidence: 99%
“…The mean TAPSE and MAPSE values according to the gestational age reported by Koestenberger et al in different studies and the mean TAPSE and MAPSE values we found in our study according to the week of gestation were consistent. [11,15] It has been reported that TAPSE value was higher than MAPSE value at any week of gestation due to the fact that dominant ventricle is the right ventricle in fetus and due to the structural characteristics of myocardial fibril distribution. [24] In our study, we found TAPSE value higher than MAPSE value, and TAPSE/MAPSE ratio was 1.37 at the second trimester while it was 1.33 at the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] There are a limited number of studies where annular plane systolic excursions of atrioventricular valves (TAPSE and MAPSE) and Tei index are assessed in healthy fetuses by M-mode echocardiography during fetal period. [12][13][14][15] In this study, we aimed to assess fetal right and left ventricle (RV and LV) functions by conventional Doppler myocardial performance index (Tei index) and tricuspid and mitral annular plane systolic excursions (TAPSE and MAPSE) in healthy fetuses, to compare the data we obtained and investigate the relationship between them.…”
Section: Introductionmentioning
confidence: 99%